Have a little faith : a true story - Albom, Mitch, frey50 (New York : Hyperion, 2009)
When an eighty-two-year-old rabbi from Albom's old hometown asks him to deliver his eulogy, Albom goes back to his nonfiction roots and becomes involved with a Detroit pastor--a reformed drug dealer and convict--who preaches to the poor and homeless in a decaying church with a hole in its roof. A timely, moving, and inspiring look at faith: not just who believes, but why.
Keywords: Albom, Mitch, -- 1958- -- Religion; Lewis, Albert L; Covington, Henry P; Faith (Judaism); Faith